Foreign Direct Investment Location Choice of Small- and Medium-Sized Enterprises: The Risk of Value Erosion of Firm-Specific Resources. - Hütt, P; Baum, M; Schwens, C; Kabst, Rüdiger (International Business Review.)

Controllers as Business Partners in Managerial Decision-Making: Attitude, Subjective Norm, and Internal Improvements. - Wolf, S; Weißenberger, B E; Wehner, M C; Kabst, Rüdiger (Journal of Accounting & Organizational Change.)

Interim Management Utilization, Firm Flexibility and its Impact on Firm Performance. - Isidor, R; Schwens, C; Kabst, Rüdiger (International Journal of Human Resources Development and Management.)

Modeling the Impact of Advertisement-Image Congruity on Applicant Attraction. - Baum, M; Schäfer, M; Kabst, Rüdiger (Human Resource Management.)

The effectiveness of recruitment advertisement and recruitment websites: Indirect and interactive effects on applicant attraction. - Baum, M; Kabst, Rüdiger (Human Resource Management (HRM).)

Recruitment Process Outsourcing and Applicant Reactions: When Does Image Make a Difference? - Wehner, M C; Giardini, A; Kabst, Rüdiger (Human Resource Management.)

The effect of culture on the responsiveness of firms to mimetic forces: Imitative foreign joint venture entries into China, 1985–2003. - Li, C; Parboteeah, P (Journal of World Business)

The influence of cultural context on the relationship between gender diversity and team performance: A meta-analysis. - Schneid, M; Isidor, R; Li, C; Kabst, Rüdiger (International Journal of Human Resource Management.)

Participatory Budgeting: Findings from Germany. - Weber, H I; Vogt, S; Eberz-Weber, L M; Steinmetz, Holger; Wagner, S A; Walther, F; Weber, P; Kabst, Rüdiger (International Journal of Public Administration in the Digital Age.)

Requirements for IT Security Metrics - An Argumentation Theory Based Approach - Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

A Multi-Theoretical Literature Review on Information Security Investments using the Resource-Based View and the Organizational Learning Theory - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (International Conference on Information Systems)
The protection of information technology (IT) has become and is predicted to remain a key economic challenge for organizations. While research on IT security investment is fast growing, it lacks a theoretical basis for structuring research, explaining economic-technological phenomena and guide future research. We address this shortcoming by suggesting a new theoretical model emerging from a multi-theoretical perspective adopt-ing the Resource-Based View and the Organizational Learning Theory. The joint appli-cation of these theories allows to conceptualize in one theoretical model the organiza-tional learning effects that occur when the protection of organizational resources through IT security countermeasures develops over time. We use this model of IT security invest-ments to synthesize findings of a large body of literature and to derive research gaps. We also discuss managerial implications of (closing) these gaps by providing practical ex-amples.
Keywords: Information Security; Investment; Literature review; Resource-based View; Organi-zational Learning Theory; Multi-theoretical Perspective

IT Security Investments Through the Lens of the Resource-Based View: A new Theoretical Model and Literature Review - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

Towards an Economic Approach to Identity and Access Management Systems Using Decision Theory - Weishäupl, Eva; Kunz, Michael; Yasasin, Emrah; Wagner, Gerit; Prester, Julian; Schryen, Guido; Pernul, Günther (2nd International Workshop on Security in highly connected IT Systems (SHCIS?15))
Nowadays, providing employees with failure-free access to various systems, applications and services is a crucial factor for organizations? success as disturbances potentially inhibit smooth workflows and thereby harm productivity. However, it is a challenging task to assign access rights to employees? accounts within a satisfying time frame. In addition, the management of multiple accounts and identities can be very onerous and time consuming for the responsible administrator and therefore expensive for the organization. In order to meet these challenges, firms decide to invest in introducing an Identity and Access Management System (IAMS) that supports the organization by using policies to assign permissions to accounts, groups, and roles. In practice, since various versions of IAMSs exist, it is a challenging task to decide upon introduction of an IAMS. The following study proposes a first attempt of a decision support model for practitioners which considers four alternatives: Introduction of an IAMS with Role-based Access Control RBAC) or without and no introduction of IAMS again with or without RBAC. To underpin the practical applicability of the proposed model, we parametrize and operationalize it based on a real world use case using input from an expert interview.
Keywords: Identity and Access Management; Economic Decision Making; Information Systems; Information Security Investment; Decision Theory

IT-Sicherheit: Ökonomisch Planen und Bewerten - Schryen, Guido; Weishäupl, Eva (Managementkompass)

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

Resource Planning in Disaster Response - Decision Support Models and Methodologies - Schryen, Guido; Rauchecker, Gerhard; Comes, Martina (Business & Information Systems Engineering (BISE))

Writing qualitative IS literature reviews ? Guidelines for synthesis, interpretation and guidance of research - Schryen, Guido (Communications of the AIS)

Discovering (Hidden) Pathways within the Framework of Design Based Research (DBR) - Developing and "Arena of Innovation" in VET Contexts - Frehe, Petra; Kremer, H.-Hugo (Crossing Boundaries in Vocational Education and Training: Innovative Concepts for the 21st Century. Conference Proceedings.)

Stochastic pumping of a polariton fluid - Assmann, Marc; Bayer, Manfred (PHYSICAL REVIEW A)
We investigate the response of a polariton laser driven slightly off-resonantly using light fields differing from the routinely studied coherent pump sources. The response to driving light fields with thermal and displaced thermal statistics with varying correlation times shows significant differences in the transmitted intensity, its noise, and the position of the nonlinear threshold. We predict that adding more photons on average may actually reduce the transmission through the polariton system.

Electric field effect on optical harmonic generation at the exciton resonances in GaAs - Brunne, D.; Lafrentz, M.; Pavlov, V. V.; Pisarev, R. V.; Rodina, A. V.; Yakovlev, D. R.; Bayer, M. (Physical Review B)
An electric field applied to a semiconductor reduces its crystal symmetry and modifies its electronic structure which is expected to result in changes of the linear and nonlinear response to optical excitation. In GaAs, we observe experimentally strong electric field effects on the optical second (SHG) and third (THG) harmonic generation. The SHG signal for the laser-light k vector parallel to the [001] crystal axis is symmetry forbidden in the electric-dipole approximation, but can be induced by an applied electric field in the vicinity of the 1s exciton energy. Surprisingly, the THG signal, which is allowed in this geometry, is considerably reduced by the electric field. We develop a theory which provides good agreement with the experimental data. In particular, it shows that the optical nonlinearities for the 1s exciton resonance are modified in an electric field by the Stark effect, which mixes the 1s and 2p exciton states of opposite parity. This mixing acts in opposite way on the SHG and THG processes, as it leads to the appearance of forbidden SHG in (001)-oriented GaAs and decreases the crystallographic THG.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Inclusive Beliefs and Self-Efficacy Concerning Inclusive Education Among German Teacher Trainees and Student Teachers - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Journal of Cognitive Education and Psychology)

„Alle außer Aaron...“ – Fallbezogene Selbstwirksamkeitserwartungen, Einstellungen und Überzeugungen zukünftiger Lehrkräfte im Kontext Inklusion - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Zeitschrift für Heilpädagogik)

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore metocean station for energy purposes - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Short term wind and energy prediction for oﬀshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (EWEA Forecasting 2015 Technology Workshop)

A Note on Decidable Separability by Piecewise Testable Languages - Czerwinski, Wojciech; Martens, Wim; van Rooijen, Lorijn; Zeitoun, Marc (Fundamentals of Computation Theory - 20th International Symposium, (FCT) 2015, Gdańsk, Poland, August 17-19, 2015, Proceedings)

Between Authenticity and Objectification: Narrating the Self in Contemporary British Drama - Tönnies, Merle (Dramatic Minds. Performance, Cognition, and the Representation of Interiority)

Mobile Agenten in Netzwerken: Analyse von Hotspots - Stilow, Georg

Integration of Wind Energy in Power System—Modelling of a Market Oriented Energy Concept - Bouyraaman, Yassin; Bendfeld, Jörg; Breymann, Philipp; Krauter, Stefan (Renewable Energy in the Service of Mankind Vol I)

Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig

Gathering a Closed Chain of Robots on a Grid - Abshoff, Sebastian; Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (arXiv:1510.05454)
We consider the following variant of the two dimensional gathering problem for swarms of robots: Given a swarm of $n$ indistinguishable, point shaped robots on a two dimensional grid. Initially, the robots form a closed chain on the grid and must keep this connectivity during the whole process of their gathering. Connectivity means, that neighboring robots of the chain need to be positioned at the same or neighboring points of the grid. In our model, gathering means to keep shortening the chain until the robots are located inside a $2× 2$ subgrid. Our model is completely local (no global control, no global coordinates, no compass, no global communication or vision, …). Each robot can only see its next constant number of left and right neighbors on the chain. This fixed constant is called the viewing path length. All its operations and detections are restricted to this constant number of robots. Other robots, even if located at neighboring or the same grid point cannot be detected. Only based on the relative positions of its detectable chain neighbors, a robot can decide to obtain a certain state. Based on this state and their local knowledge, the robots do local modifications to the chain by moving to neighboring grid points without breaking the chain. These modifications are performed without the knowledge whether they lead to a global progress or not. We assume the fully synchronous $\mathcal{FSYNC}$ model. For this problem, we present a gathering algorithm which needs linear time. This result generalizes the result from \cite{hopper}, where an open chain with specified distinguishable (and fixed) endpoints is considered.

Approximation and Heuristic Algorithms for Computing Backbones in Asymmetric Ad-Hoc Networks - Abu-Khzam, Faisal N.; Markarian, Christine; Meyer auf der Heide, Friedhelm; Schubert, Michael (arXiv:1510.01866)
We consider the problem of dominating set-based virtual backbone used for routing in asymmetric wireless ad-hoc networks. These networks have non-uniform transmission ranges and are modeled using the well-established disk graphs. The corresponding graph theoretic problem seeks a strongly connected dominating-absorbent set of minimum cardinality in a digraph. A subset of nodes in a digraph is a strongly connected dominating-absorbent set if the subgraph induced by these nodes is strongly connected and each node in the graph is either in the set or has both an in-neighbor and an out-neighbor in it. Distributed algorithms for this problem are of practical significance due to the dynamic nature of ad-hoc networks. We present a first distributed approximation algorithm, with a constant approximation factor and O(Diam) running time, where Diam is the diameter of the graph. Moreover we present a simple heuristic algorithm and conduct an extensive simulation study showing that our heuristic outperforms previously known approaches for the problem.

Online Top-k-Position Monitoring of Distributed Data Streams - Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 29th International Parallel and Distributed Processing Symposium (IPDPS))
Consider n nodes connected to a single coordinator. Each node receives an individual online data stream of numbers and, at any point in time, the coordinator has to know the k nodes currently observing the largest values, for a given k between 1 and n. We design and analyze an algorithm that solves this problem while bounding the amount of messages exchanged between the nodes and the coordinator. Our algorithm employs the idea of using filters which, intuitively speaking, leads to few messages to be sent, if the new input is "similar" to the previous ones. The algorithm uses a number of messages that is on expectation by a factor of O((log Δ + k) log n) larger than that of an offline algorithm that sets filters in an optimal way, where Δ is upper bounded by the largest value observed by any node.

Discrete variational Lie group formulation of geometrically exact beam dynamics - Demoures, F.; Gay-Balmaz, F.; Leyendecker, S.; Ober-Blöbaum, S.; Ratiu, T. S.; Weinand, Y. (Numerische Mathematik)

PFC-control for improved inductor utilization - Keuck, L.; Frohleke, N.; Bocker, J.; Ziessler, A. (2015 17th European Conference on Power Electronics and Applications (EPE'15 ECCE-Europe))

Multiobjective optimal control of fluid mixing - Ober-Blöbaum, Sina; Padberg-Gehle, Kathrin (PAMM)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, Maik; Ober-Blöbaum, Sina; Leyendecker, Sigrid (PAMM)

MIFID II Wertpapierhandel und -beratung in Veränderung - Krimphove, Dieter (Zeitschrift für das gesamte Kreditwesen (ZfgK))

Nonlinear optical sub-bandgap excitation of ZnO-based photonic resonators - Bader, Christina A.; Zeuner, Franziska; Bader, Manuel H. W.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Broadband Hybrid Holographic Multiplexing with Geometric Metasurfaces - Huang, Lingling; Mühlenbernd, Holger; Li, Xiaowei; Song, Xu; Bai, Benfeng; Wang, Yongtian; Zentgraf, Thomas (Advanced Materials)

Continuous control of the nonlinearity phase for harmonic generations - Li, Guixin; Chen, Shumei; Pholchai, Nitipat; Reineke, Bernhard; Wong, Polis Wing Han; Pun, Edwin Yue Bun; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nature Materials)

Metasurface holograms reaching 80% efficiency - Zheng, Guoxing; Mühlenbernd, Holger; Kenney, Mitchell; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nature Nanotechnology)

Symmetry exploiting control of hybrid mechanical systems - Flasskamp, Kathrin; Hage-Packhäuser, Sebastian; Ober-Blöbaum, Sina (Journal of Computational Dynamics)

High order variational integrators in the optimal control of mechanical systems - Campos, Cédric M.; Ober-Blöbaum, Sina; Trélat, Emmanuel (Discrete & Continuous Dynamical Systems - A)

A gender perspective on business process management competences offered on professional online social networks - Gorbacheva, Elena; Stein, Armin; Schmiedel, Theresa; Müller, Oliver (European Conference on Information Systems)

Potenzialbeurteilung neuer Technologien im Prozesscontrolling - vom Brocke, Jan; Müller, Oliver; Debortoli, Stefan; Reuter, Nadine (Controlling)

Self-Optimizing Organic Cache - Ahmed, Abdullah Fathi

Management and Scheduling of Accelerators for Heterogeneous High-Performance Computing - Beisel, Tobias
The use of heterogeneous computing resources, such as graphics processing units or other specialized co-processors, has become widespread in recent years because of their performance and energy efficiency advantages. Operating system approaches that are limited to optimizing CPU usage are no longer sufficient for the efficient utilization of systems that comprise diverse resource types. Enabling task preemption on these architectures and migration of tasks between different resource types at run-time is not only key to improving the performance and energy consumption but also to enabling automatic scheduling methods for heterogeneous compute nodes. This thesis proposes novel techniques for run-time management of heterogeneous resources and enabling tasks to migrate between diverse hardware. It provides fundamental work towards future operating systems by discussing implications, limitations, and chances of the heterogeneity and introducing solutions for energy- and performance-efficient run-time systems. Scheduling methods to utilize heterogeneous systems by the use of a centralized scheduler are presented that show benefits over existing approaches in varying case studies.

Evolution of Heat Flow Prediction Models for FPGA Devices - Hangmann, Hendrik

Computer Vision basierte Klassifikation von HD EMG Signalen - Haupt, Christian

Microarchitectural optimization by means of reconfigurable and evolvable cache mappings - Ho, Nam; Ahmed, Abdullah Fathi; Kaufmann, Paul; Platzner, Marco (Proc. NASA/ESA Conf. Adaptive Hardware and Systems (AHS))
Keywords: cache storage; field programmable gate arrays; multiprocessing systems; parallel architectures; reconfigurable architectures; FPGA; dynamic reconfiguration; evolvable cache mapping; many-core architecture; memory-to-cache address mapping function; microarchitectural optimization; multicore architecture; nature-inspired optimization; parallelization degrees; processor; reconfigurable cache mapping; reconfigurable computing; Field programmable gate arrays; Software; Tuning

Generator Start-up Sequences Optimization for Network Restoration Using Genetic Algorithm and Simulated Annealing - Kaufmann, Paul; Shen, Cong (Genetic and Evolutionary Computation (GECCO))

Comparison of thread signatures for error detection in hybrid multi-cores - Meisner, Sebastian; Platzner, Marco (Field Programmable Technology (FPT), 2015 International Conference on)

Konzept und Implementation einer Benutzeroberfläche zur Generierung virtueller FPGAs - Meißner, Roland

Acceleration of Artificial Neural Networks on a Zynq Platform - Posewsky, Thorbjörn

Applications of Evolutionary Computation - 18th European Conference, EvoApplications - M. Mora, Antonio; Squillero, Giovanni; Agapitos, Alexandros; Burelli, Paolo; S. Bush, William; Cagnoni, Stefano; Cotta, Carlos; De Falco, Ivanoe; Della Cioppa, Antonio; Divina, Federico; Eiben, A.E.; I. Esparcia-Alcázar, Anna; et al.

Significant papers from the first 25 years of the FPL conference - H.W. Leong, Philip; Amano, Hideharu; Anderson, Jason; Bertels, Koen; M.P. Cardoso, João; Diessel, Oliver; Gogniat, Guy; Hutton, Mike; Lee, JunKyu; Luk, Wayne; Lysaght, Patrick; Platzner, Marco; et al. (Proceedings of the 25th International Conference on Field Programmable Logic and Applications (FPL))

New Codesign Solutions for Modelling and Partitioning of Probabilistic Reconfigurable Embedded Software - Ghribi, Ines; Ben Abdallah, Riadh; Khalgui, Mohamed; Platzner, Marco (Proceedings of the 29th European Simulation and Modelling Conference (ESM))

From Defect Analysis to Gate-Level Fault Modeling of Controllable-Polarity Silicon Nanowires - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; De Micheli, Giovanni (IEEE Transactions on Nanotechnology)

On the design of a fault tolerant ripple-carry adder with controllable-polarity transistors - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; Zhang, Jian; De Micheli, Giovanni; Sanchez, Eduardo; Reorda, Matteo Sonza (2015 IEEE Computer Society Annual Symposium on VLSI)

Fault modeling in controllable polarity silicon nanowire circuits - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; De Micheli, Giovanni (Proceedings of the 2015 Design, Automation & Test in Europe Conference & Exhibition)

Over effective hard real-time hardware tasks scheduling and allocation - Guettatfi, Zakarya; Kermia, Omar; Khouas, Abdelhakim (25th International Conference on Field Programmable Logic and Applications (FPL))
Keywords: embedded systems; field programmable gate arrays; operating systems (computers); scheduling; μC/OS-II; FPGAs; OS foundation; SafeRTOS; Xenomai; chip utilization ration; complex time constraints; embedded systems; hard real-time hardware task allocation; hard real-time hardware task scheduling; hardware-software real-time operating systems; partially reconfigurable field-programmable gate arrays; resource constraints; safety-critical RTOS; Field programmable gate arrays; Hardware; Job shop scheduling; Real-time systems; Shape; Software

On Optimal Smoothing in Minimum Statistics Based Noise Tracking - Chinaev, Aleksej; Haeb-Umbach, Reinhold (Interspeech 2015)
Noise tracking is an important component of speech enhancement algorithms. Of the many noise trackers proposed, Minimum Statistics (MS) is a particularly popular one due to its simple parameterization and at the same time excellent performance. In this paper we propose to further reduce the number of MS parameters by giving an alternative derivation of an optimal smoothing constant. At the same time the noise tracking performance is improved as is demonstrated by experiments employing speech degraded by various noise types and at different SNR values.
Keywords: speech enhancement; noise tracking; optimal smoothing

Semantic Analysis of Spoken Input using Markov Logic Networks - Despotovic, Vladimir; Walter, Oliver; Haeb-Umbach, Reinhold (INTERSPEECH 2015)
We present a semantic analysis technique for spoken input using Markov Logic Networks (MLNs). MLNs combine graphical models with first-order logic. They areparticularly suitable for providing inference in the presence of inconsistent and incomplete data, which are typical of an automatic speech recognizer's (ASR) output in the presence of degraded speech. The target application is a speech interface to a home automation system to be operated by people with speech impairments, where the ASR output is particularly noisy. In order to cater for dysarthric speech with non-canonical phoneme realizations, acoustic representations of the input speech are learned in an unsupervised fashion. While training data transcripts are not required for the acoustic model training, the MLN training requires supervision, however, at a rather loose and abstract level. Results on two databases, one of them for dysarthric speech, show that MLN-based semantic analysis clearly outperforms baseline approaches employing non-negative matrix factorization, multinomial naive Bayes models, or support vector machines.

DOA-Estimation based on a Complex Watson Kernel Method - Drude, Lukas; Jacob, Florian; Haeb-Umbach, Reinhold (23th European Signal Processing Conference (EUSIPCO 2015))
This contribution presents a Direction of Arrival (DoA) estimation algorithm based on the complex Watson distribution to incorporate both phase and level differences of captured micro- phone array signals. The derived algorithm is reviewed in the context of the Generalized State Coherence Transform (GSCT) on the one hand and a kernel density estimation method on the other hand. A thorough simulative evaluation yields insight into parameter selection and provides details on the performance for both directional and omni-directional microphones. A comparison to the well known Steered Response Power with Phase Transform (SRP-PHAT) algorithm and a state of the art DoA estimator which explicitly accounts for aliasing, shows in particular the advantages of presented algorithm if inter-sensor level differences are indicative of the DoA, as with directional microphones.

BLSTM supported GEV Beamformer Front-End for the 3RD CHiME Challenge - Heymann, Jahn; Drude, Lukas; Chinaev, Aleksej; Haeb-Umbach, Reinhold (Automatic Speech Recognition and Understanding Workshop (ASRU 2015))

Unsupervised adaptation of a denoising autoencoder by Bayesian Feature Enhancement for reverberant asr under mismatch conditions - Heymann, Jahn; Haeb-Umbach, Reinhold; Golik, P.; Schlueter, R. (Acoustics, Speech and Signal Processing (ICASSP), 2015 IEEE International Conference on)
The parametric Bayesian Feature Enhancement (BFE) and a datadriven Denoising Autoencoder (DA) both bring performance gains in severe single-channel speech recognition conditions. The first can be adjusted to different conditions by an appropriate parameter setting, while the latter needs to be trained on conditions similar to the ones expected at decoding time, making it vulnerable to a mismatch between training and test conditions. We use a DNN backend and study reverberant ASR under three types of mismatch conditions: different room reverberation times, different speaker to microphone distances and the difference between artificially reverberated data and the recordings in a reverberant environment. We show that for these mismatch conditions BFE can provide the targets for a DA. This unsupervised adaptation provides a performance gain over the direct use of BFE and even enables to compensate for the mismatch of real and simulated reverberant data.
Keywords: codecs; signal denoising; speech recognition; Bayesian feature enhancement; denoising autoencoder; reverberant ASR; single-channel speech recognition; speaker to microphone distances; unsupervised adaptation; Adaptation models; Noise reduction; Reverberation; Speech; Speech recognition; Training; deep neuronal networks; denoising autoencoder; feature enhancement; robust speech recognition

Absolute Geometry Calibration of Distributed Microphone Arrays in an Audio-Visual Sensor Network - Jacob, Florian; Haeb-Umbach, Reinhold (ArXiv e-prints)
Joint audio-visual speaker tracking requires that the locations of microphones and cameras are known and that they are given in a common coordinate system. Sensor self-localization algorithms, however, are usually separately developed for either the acoustic or the visual modality and return their positions in a modality specific coordinate system, often with an unknown rotation, scaling and translation between the two. In this paper we propose two techniques to determine the positions of acoustic sensors in a common coordinate system, based on audio-visual correlates, i.e., events that are localized by both, microphones and cameras separately. The first approach maps the output of an acoustic self-calibration algorithm by estimating rotation, scale and translation to the visual coordinate system, while the second solves a joint system of equations with acoustic and visual directions of arrival as input. The evaluation of the two strategies reveals that joint calibration outperforms the mapping approach and achieves an overall calibration error of 0.20m even in reverberant environments.

Robust Automatic Speech Recognition - Li, Jinyu; Deng, Li; Haeb-Umbach, Reinhold; Gong, Y.

Typicality and Emotion in the Voice of Children with Autism Spectrum Condition: Evidence Across Three Languages - Marchi, Erik; Schuller, Bjoern; Baron-Cohen, Simon; Golan, Ofer; Boelte, Sven; Arora, Prerna; Haeb-Umbach, Reinhold (INTERSPEECH 2015)
Only a few studies exist on automatic emotion analysis of speech from children with Autism Spectrum Conditions (ASC). Out of these, some preliminary studies have recently focused on comparing the relevance of selected prosodic features against large sets of acoustic, spectral, and cepstral features; however, no study so far provided a comparison of performances across different languages. The present contribution aims to fill this white spot in the literature and provide insight by extensive evaluations carried out on three databases of prompted phrases collected in English, Swedish, and Hebrew, inducing nine emotion categories embedded in short-stories. The datasets contain speech of children with ASC and typically developing children under the same conditions. We evaluate automatic diagnosis and recognition of emotions in atypical childrens voice over the nine categories including binary valence/arousal discrimination.

Source Counting in Speech Mixtures by Nonparametric Bayesian Estimation of an infinite Gaussian Mixture Model - Walter, Oliver; Drude, Lukas; Haeb-Umbach, Reinhold (40th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2015))
In this paper we present a source counting algorithm to determine the number of speakers in a speech mixture. In our proposed method, we model the histogram of estimated directions of arrival with a nonparametric Bayesian infinite Gaussian mixture model. As an alternative to classical model selection criteria and to avoid specifying the maximum number of mixture components in advance, a Dirichlet process prior is employed over the mixture components. This allows to automatically determine the optimal number of mixture components that most probably model the observations. We demonstrate by experiments that this model outperforms a parametric approach using a finite Gaussian mixture model with a Dirichlet distribution prior over the mixture weights.

Autonomous Learning of Representations - Walter, Oliver; Haeb-Umbach, Reinhold; Mokbel, Bassam; Paassen, Benjamin; Hammer, Barbara (KI - Kuenstliche Intelligenz)
Besides the core learning algorithm itself, one major question in machine learning is how to best encode given training data such that the learning technology can efficiently learn based thereon and generalize to novel data. While classical approaches often rely on a hand coded data representation, the topic of autonomous representation or feature learning plays a major role in modern learning architectures. The goal of this contribution is to give an overview about different principles of autonomous feature learning, and to exemplify two principles based on two recent examples: autonomous metric learning for sequences, and autonomous learning of a deep representation for spoken language, respectively.
Keywords: Representation learning; Metric learning; Deep representation; Spoken language

Lexicon Discovery for Language Preservation using Unsupervised Word Segmentation with Pitman-Yor Language Models (FGNT-2015-01) - Walter, Oliver; Haeb-Umbach, Reinhold; Strunk, Jan; P. Himmelmann, Nikolaus
In this paper we show that recently developed algorithms for unsupervised word segmentation can be a valuable tool for the documentation of endangered languages. We applied an unsupervised word segmentation algorithm based on a nested Pitman-Yor language model to two austronesian languages, Wooi and Waima'a. The algorithm was then modified and parameterized to cater the needs of linguists for high precision of lexical discovery: We obtained a lexicon precision of of 69.2% and 67.5% for Wooi and Waima'a, respectively, if single-letter words and words found less than three times were discarded. A comparison with an English word segmentation task showed comparable performance, verifying that the assumptions underlying the Pitman-Yor language model, the universality of Zipf's law and the power of n-gram structures, do also hold for languages as exotic as Wooi and Waima'a.

Making cars a main ICT resource in smart cities - Altintas, Onur; Dressler, Falko; Hagenauer, Florian; Matsumoto, Makiko; Sepulcre, Miguel; Sommer, Christoph (2015 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Timings Matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (ACM SIGMOBILE Mobile Computing and Communications Review)

Power matters: Automatic Gain Control for a Software Defined Radio IEEE 802.11a/g/p receiver - Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2015 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

The scrambler attack: A robust physical layer attack on location privacy in vehicular networks - Bloessl, Bastian; Sommer, Christoph; Dressier, Falko; Eckhoff, David (2015 International Conference on Computing, Networking and Communications (ICNC))

Simulative performance evaluation of vehicular networks - Eckhoff, David; Sommer, Christoph (Vehicular Communications and Networks)

Poster: A simulator for heterogeneous vehicular networks - Hagenauer, Florian; Dressler, Falko; Sommer, Christoph (2014 IEEE Vehicular Networking Conference (VNC))

Fairness kills safety: A comparative study for intersection assistance applications - Joerer, Stefan; Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Cigno, Renato Lo; Dressler, Falko (2014 IEEE 25th Annual International Symposium on Personal, Indoor, and Mobile Radio Communication (PIMRC))

Enabling Situation Awareness at Intersections for IVC Congestion Control Mechanisms - Joerer, Stefan; Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Cigno, Renato Lo; Jamalipour, Abbas; Dressler, Falko (IEEE Transactions on Mobile Computing)

MCB – A multi-channel beaconing protocol - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (Ad Hoc Networks)